Analisis Komparatif Metode Manufaktur Soft Pneumatic Actuator Berdasarkan Biaya, Waktu Fabrikasi, dan Karakteristik Mekanik - Ilham Saputra; Irfan Bahiuddin; Bambang Hari Priyambodo; Efrem Olivio Gomes; Adhan Efendi (Infotekmesin, 2026)
The rapid development of soft pneumatic actuators (SPAs) has driven a transition in manufacturing approaches from elastomer-based casting to additive manufacturing (AM). Although both methods have been widely adopted, systematic comparative studies to support manufacturing method selection remain limited. This study proposes a comparative evaluation framework to assess casting and additive manufacturing based on three key parameters: relative cost, fabrication time, and mechanical characteristics. The analysis was conducted through a structured literature review and semi-quantitative synthesis of 29 publications published between 2015 and 2025. The results indicate that casting provides lower material costs and superior structural homogeneity, whereas additive manufacturing offers greater design flexibility, more complex internal geometries, and higher production repeatability. The proposed evaluation framework provides a conceptual basis for selecting the most appropriate SPA manufacturing method according to application requirements, production scale, and available resources.